-30-6x=-6(3x-7)

Simple and best practice solution for -30-6x=-6(3x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -30-6x=-6(3x-7) equation:


Simplifying
-30 + -6x = -6(3x + -7)

Reorder the terms:
-30 + -6x = -6(-7 + 3x)
-30 + -6x = (-7 * -6 + 3x * -6)
-30 + -6x = (42 + -18x)

Solving
-30 + -6x = 42 + -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
-30 + -6x + 18x = 42 + -18x + 18x

Combine like terms: -6x + 18x = 12x
-30 + 12x = 42 + -18x + 18x

Combine like terms: -18x + 18x = 0
-30 + 12x = 42 + 0
-30 + 12x = 42

Add '30' to each side of the equation.
-30 + 30 + 12x = 42 + 30

Combine like terms: -30 + 30 = 0
0 + 12x = 42 + 30
12x = 42 + 30

Combine like terms: 42 + 30 = 72
12x = 72

Divide each side by '12'.
x = 6

Simplifying
x = 6

See similar equations:

| 17x+6=106 | | 16-3m=7-6(m+2) | | 10x-25=105 | | 80+x=171 | | 34+4x=-5(x+4) | | -3x-3(1+1)=-15 | | 55x=605 | | 2x+-2=10-4 | | 4y+9=17-2y | | 43+x=410 | | x-24=64 | | -3X^2+90=0 | | 5x=430 | | 4x-5y-9x+8y=0 | | 2x^2-lnx+1=0 | | 90-x^2=0 | | -x+3+12x=-4+4x+42 | | 5x-15x^3=5x(1-3x^2) | | (x+8)+4=x+(4+8) | | 3w^2-10w+8=0 | | -4(2+3n)=-56 | | 2(a+3)=5a-1 | | -4-4(2+4v)=-44 | | a-4(2a+4)=-44 | | 10a=45 | | 3(2+4x)=-42 | | 5(y^2-14y+49)=-90 | | 5x-12a=7-2x | | 2.4(m-3)+3.8=-32 | | 3x(x)+8x=9 | | 10n^2-9n=9 | | 6(y+x+2+x+4)=18 |

Equations solver categories